2022
DOI: 10.3390/molecules27103093
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic Extract from Pteris wallichiana Alleviates DSS-Induced Intestinal Inflammation and Intestinal Barrier Dysfunction by Inhibiting the TLR4/NF-κB Pathway and Regulating Tight Junction Proteins

Abstract: The aim of the research was to determine the protective effect and mechanism of Pteris wallichiana J. Agardh extract (PWE) on DSS-induced ulcerative colitis (UC) in mice. In this research, PWE is rich in flavonoids and diterpenoids by UPLC-MS/MS analysis. In LPS-induced RAW264.7 cells, PWE reduced the productions of inflammatory factors (i.e., NO, TNF-α, IL-6, and IL-1β). In DSS-induced UC in mice, PWE improved disease activity index (DAI) score, attenuated oxidative stress by decreasing MPO and MDA activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…According to a previous study, TLR4/MyD88/NF-κB signaling is associated with intestinal inflammation in UC [52,53], and DEX was shown to inhibit TLR4/MyD88/NF-κB signaling in septic acute kidney injury [54]. Therefore, whether DEX can regulate this pathway in the experimental UC model was investigated in our study.…”
Section: Discussionmentioning
confidence: 90%
“…According to a previous study, TLR4/MyD88/NF-κB signaling is associated with intestinal inflammation in UC [52,53], and DEX was shown to inhibit TLR4/MyD88/NF-κB signaling in septic acute kidney injury [54]. Therefore, whether DEX can regulate this pathway in the experimental UC model was investigated in our study.…”
Section: Discussionmentioning
confidence: 90%
“…24,25 ZO-1, occludin, JAM2 and claudin-1 are intestinal epithelial tight junction proteins, which play an important role in maintaining the integrity of intestinal epithelia. 26 MUC2, distributed in small intestine and large intestine, is the main component of the intestinal mucus layer, and the contents of MUC2 can strengthen the intestinal barrier. 27 In this study, our data indicated that LPS significantly increased the DAO activity and the D-LA content in serum and decreased the mRNA expression of tight junction protein related genes ZO-1, occludin, claudin-1, MUC2 and JAM2 in jejunum of mice.…”
Section: Papermentioning
confidence: 99%
“…At 0.3%, kaempferol ( 10 ) decreased the plasma leukotriene B4 [LTB(4)] level in all treated animals, while NO and PGE2 contents decreased significantly [ 110 ]. Kaempferol ( 10 ) also suppressed MPO activity in the colon mucosa [ 114 ]. Additionally, in kaempferol ( 10 ) pre-treated animals, the quantity of TFF3 (a marker of goblet cell function) mRNA was upregulated, indicating its usefulness [ 110 , 115 ].…”
Section: Bioactive Components Of M Oleifera and Th...mentioning
confidence: 99%